Pengembangan Media Pembelajaran Daring “Si Pipa” Berbasis Aplikasi Android pada Pembelajaran Matematika Materi Pecahan Kelas IV SD - Aisyah Fatma Anggraeni; Ervina Eka Subekti; Fine Reffiane (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine whether the learning media "Si Pipa" is suitable for use as a medium for learning mathematics for grade IV elementary school fraction materials and to determine whether the development of media "Si Pipa" in learning mathematics for grade IV fractions meets the valid value. The type of research applied to this research is research and development (RnD). The samples taken were 20  fourth grade students of SD Negeri 2 Pengkol Jepara using probability sampling technique. The data in this study were obtained through interviews and questionnaires. The results of the assessment from media experts reached an average percentage of 93.23% with the criteria of "very good". The results of the assessment from material experts reached an average percentage of 91.35% with the criteria of "very good". The results of the media acceptance assessment by fourth grade teachers reached a percentage of 94.44% with the criteria of "very good", then the results of field trials from fourth grade students reached an average of 93.68% with the criteria of "very good".